Environmental Impacts of Tigray War: Evidence from 2020-2026 - Daniel Girmay Teka; Haregot Zeray Hagos; Nigisti Beyene; Rshan Haile Tsehaye; Samuel Atalkti; Girmay Gebrehiwot (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
This paper endeavors to analyze the environmental impact caused by the Tigray War in northern Ethiopia between 2020 and 2026. The study specifically examines the effect of the war on deforestation, soil erosion, destruction of water resources, biodiversity loss, as well as the indirect impacts including biomass usage in siege environments. Besides, it also highlights some of the lacunas found in existing literature regarding this issue and the priorities for environmental recovery following the war. The method adopted is qualitative desk review of peer reviewed papers, institutional and governmental reports and NGO papers The literature review reveals that Tigray War has undone all the efforts made for the past several decades for environmental rehabilitation in the region. Deforestation, collapse of soil and water conservation works, serious land degradation, and disturbance of watersheds are among the negative impacts observed in the area. Also, through remote sensing data, significant loss of vegetation cover can be noted in the regions affected by war. Furthermore, the indirect environmental impacts like high biomass consumption in siege environments have also been observed. The study bases its findings in the global theories on war and the environment that include concepts such as ecocide and the war ecology theory. According to this study, the Tigray war created a serious socio-ecological crisis that negates all the environmental improvements that have been made over the past few decades, making a close link between environmental destruction and humanitarian/ livelihood crises. Based on the findings above, the recommendations are that ecosystem restoration be undertaken through reforestation, restoration of water and soil conservation infrastructure and environmental governance institutions. Further research is needed on the long-term effects of ecological recovery and post-conflict resilience of communities in Tigray.